Expression of Protein Acetylation Regulators During Peripheral Nerve Development, Injury, and Regeneration - Sun, Junjie; Ji, Yuhua; Liang, Qingyun; Ming, Mengru; Chen, Yuhan; Zhang, Qi; Zhou, Songlin; Shen, Mi; Ding, Fei (Frontiers in Molecular Neuroscience, 2022)
Protein acetylation, regulated by acetyltransferases and deacetylases, is an important post-translational modification that is involved in numerous physiological and pathological changes in peripheral nerves. There is still no systematical analysis on the expression changes of protein acetylation regulators during sciatic nerve development, injury and regeneration. Here, we sequenced and analyzed the transcriptome of mouse sciatic nerves during development and after injury. We found that the changes in the expression of most regulators followed the rule that "development is consistent with regeneration and opposite to injury." Immunoblotting with pan-acetylated antibodies also revealed that development and regeneration are a process of increased acetylation, while injury is a process of decreased acetylation. Moreover, we used bioinformatics methods to analyze the possible downstream molecules of two key regulators, histone deacetylase 1 (hdac1) and lysine acetyltransferase 2b (kat2b), and found that they were associated with many genes that regulate the cell cycle. Our findings provide an insight into the association of sciatic nerve development, injury and regeneration from the perspective of protein acetylation.